Ugotavljanje dejanskega stanja na prvi in drugi stopnji v pravdnem postopku - Galič, Aleš (Podjetje in delo, 2017)
The latest amendment of the Civil Procedure Act does not introduce any groundbreaking changes in the structure of Slovenian civil procedure. It does however provide for certain changes that shall influence the activities of judges both at the lower and appellate courts concerning establishing disputed facts. For the first instance judges, changes concerning taking of evidence shall be of a particular importance, e.g. broadening the scope of disclosure of documents, the possibility for the court to appoint an expert already in the pre-action phase, but also the instruments aimed at protection of trade secrets in civil procedures. Concerning appellate courts, the legislature has again tried to promote a higher number of oral hearings in those courts, which might, hopefully, decrease the number of cases where the appellate court merely quashes the judgment and refers it back to the first instance court for a retrial.
Keywords: civil procedure; disclosure of evidence; dokazi; evidence; poslovna skrivnost; pravdni postopek; pravica do pritožbe; razkritje dokazov; right to appeal; trade secrets